Amplified fragment length polymorphism in Mycosphaerella graminicola - Kabbage, Mehdi (Kansas State University, 2007)
Septoria tritici blotch caused by Mycosphaerella graminicola (anamorph Septoria tritici), is an important disease of wheat worldwide capable of reducing yields by as much as 30 to 40%. In Kansas, the disease is widespread and losses in individual fields can exceed 25%. This study examined the genetic structure of Kansas populations of M. graminicola at different spatial scales (micro-plot, macro-plot, and statewide) using amplified fragment length polymorphism (AFLP) markers. Three primer pairs were used to resolve 174 polymorphic loci from 476 isolates. The results indicated high levels of genotypic variability, which is consistent with a genetically diverse initial inoculum. Genetic identities among populations representing the three spatial scales were >98%. Tests for differentiation among populations due to population subdivision revealed that on average 97.5% of the genetic variability occurred within populations with a correspondingly high migration rate of 16 to 23 individuals per generation. We observed little evidence of linkage disequilibrium, on average, only 4.6% of locus pairs were in disequilibrium. Our results indicate that Kansas populations of M. graminicola are characterized by regular recombination, are genetically diverse, and appear to be homogenous across different spatial scales. These populations are probably components of a larger pathogen pool that is distributed at least across much of Kansas and probably the central Great Plains. Because of the frequent recombination, the risk of adaptation of Kansas populations of M. graminicola to fungicide treatments or resistance genes is high and could be dispersed very quickly, whether these new pathogenic traits occur locally through mutation or by migration from other areas.
Keywords: Mycosphaerella; Aflp; Agriculture, Plant Pathology (0480)